Large-Area Perovskite Solar Module Produced by Introducing Self-Assembled L-Histidine Monolayer at TiO2 and Perovskite Interface - Hung-Chieh Hsu; Jung-Che Tsao; Cheng-Hsien Yeh; Hsuan-Ta Wu; Chien-Te Wu; Shih-Hsiung Wu; Chuan-Feng Shih (Nanomaterials, 2024)
Perovskite solar cells have been proven to enhance cell characteristics by introducing passivation materials that suppress defect formation. Defect states between the electron transport layer and the absorption layer reduce electron extraction and carrier transport capabilities, leading to a significant decline in device performance and stability, as well as an increased probability of non-radiative recombination. This study proposes the use of an amino acid (L-Histidine) self-assembled monolayer material between the transport layer and the perovskite absorption layer. Surface analysis revealed that the introduction of L-Histidine improved both the uniformity and roughness of the perovskite film surface. X-ray photoelectron spectroscopic analysis showed a reduction in oxygen vacancies in the lattice and an increase in Ti4+, indicating that L-Histidine successfully passivated trap states at the perovskite and TiO2 electron transport layer interface. In terms of device performance, the introduction of L-Histidine significantly improved the fill factor (FF) because the reduction in interface defects could suppress charge accumulation and reduce device hysteresis. The FF of large-area solar modules (25 cm2) with L-Histidine increased from 55% to 73%, and the power conversion efficiency (PCE) reached 16.5%. After 500 h of aging tests, the PCE still maintained 91% of its original efficiency. This study demonstrates the significant impact of L-Histidine on transport properties and showcases its potential for application in the development of large-area perovskite module processes.